HL‐TWiM Empirical Model of High‐Latitude Upper Thermospheric Winds. Issue 12 (19th December 2019) - Dhadly, Manbharat S.; Emmert, John T.; Drob, Douglas P.; Conde, Mark G.; Aruliah, Anasuya; Doornbos, Eelco; Shepherd, Gordon G.; Wu, Qian; Makela, Jonathan J.; Niciejewski, Rick J.; Lee, Changsup; Jee, Geonhwa; et al.
Abstract: We present an empirical model of thermospheric winds (High‐latitude Thermospheric Wind Model [HL‐TWiM]) that specifies F region high‐latitude horizontal neutral winds as a function of day of year, latitude, longitude, local time, and geomagnetic activity. HL‐TWiM represents the large‐scale neutral wind circulation, in geomagnetic coordinates, for the given input conditions. The model synthesizes the most extensive collection to date of historical high‐latitude wind measurements; it is based on statistical analyses of several decades of F region thermospheric wind measurements from 21 ground‐based stations (Fabry‐Perot Interferometers and Scanning Doppler Imaging Fabry‐Perot Interferometers) located at various northern and southern high latitudes and two space‐based instruments (UARS WINDII and GOCE). The geomagnetic latitude and local time dependences in HL‐TWiM are represented using vector spherical harmonics, day of year and longitude variations are represented using simple harmonic functions, and the geomagnetic activity dependence is represented using quadratic B splines. In this paper, we describe the HL‐TWiM formulation and fitting procedures, and we verify the model against the neutral wind databases used in its formulation. HL‐TWiM provides a necessary benchmark for validating new wind observations and tuning our physical understanding of complex wind behaviors. Results show stronger Universal Time variation in winds at southern than northern high latitudes. Model‐data intra‐annual comparisons in this study show semiannual oscillation‐like behavior of GOCE winds, rarely observed before in wind data. Key Points: We developed a comprehensive empirical model of high‐latitude F region thermospheric winds (HL‐TWiM) Universal Time variations in high‐latitude winds are stronger in the Southern than Northern Hemisphere HL‐TWiM provides a necessary benchmark for validating new high‐latitude wind observations and tuning first principal models